Analysis of Validity and Reliability of Self-Acceptance Scale Using Rasch Model - Faraz Maulana Gunawan; Dodi Suryana; Hyunisa Rahmanadia (LPPM Universitas Terbuka, 2023)
The measurement of self-acceptance in previous studies still uses classical methods. A valid and reliable self-acceptance scale will help measure the ability to recognize, accept oneself for uniqueness. This study aims to validate and develop the Self-Acceptance Scale. This study was conducted on 100 high school students in Lembang, West Java Province, which included 58 females and 42 males. Cross-sectional survey research methods and a quantitative methodology were employed in this study. The Rasch Model was utilized for data analysis with the Win steps 3.73 program. The findings indicated that 25 items and four scale alternatives where The Cronbach Alpha value represents the interaction between Person and Item is in the excellent category with a value of 0.56. A person's reliability is in a suitable category with a value of 0.47, which indicates the consistency of respondents' answers. The scale meets the criteria that can be used to measure student self-acceptance.